See You On TV: A Phenomenology of Careers on Extension Television in Oklahoma - Austin R Moore; Erica Irlbeck (Journal of Applied Communications, 2021)
Extension specialists are under increasing pressure to interact with audiences through emerging digital media including video. In an effort to understand how such interactions affect the careers of engaged specialists, this study seeks to explore the career effects on Extension subject-matter specialists that resulted from long-term, regular participation in an Extension television effort. Using Cultivation theory and source credibility as a lens, a qualitative phenomenology was conducted by interviewing individuals who have contributed to one such program on a weekly or bi-weekly program for multiple decades. Participants reported improved career effectiveness via increased credibility in face to face communications as well as enhanced communication when broadcast messages were seen as a continuation of in-person communications. Early career advancement was said to have resulted in spite of broadcast participation rather than as a result of participation, however, administrative attitudes toward broadcast have shifted in favor of such efforts.
Keywords: Extension Television; Video; Broadcasting; Source Credibility; Two-way Communication